Operator Equations for Eddy Currents on Singular Carriers - Naumenko, Jan (Matrix Methods: Theory, Algorithms And Applications, 2010)
The problem of eddy currents computation on the conducting surface is considered. It is reduced to the integral equations. The existence, uniqueness and stability of their solutions is proved. The numerical method for the mentioned problem is described. The example of computing is given.